ChemInform Abstract: One‐Pot Synthesis of Arylketones from Aromatic Acids via Palladium‐Catalyzed Suzuki Coupling. Issue 32 (July 2016) - Wu, Hongxiang; Xu, Baiping; Li, Yue; Hong, Fengying; Zhu, Dezhao; Jian, Junsheng; Pu, Xiaoer; Zeng, Zhuo
Abstract: 2‐Chloro‐4, 6‐dimethoxy‐1, 3, 5‐triazine is used to form an intermediary triazenyl ester which undergoes the coupling reaction.